The significance of intraoperative fluorescence angiography in miniinvasive low rectal resections - Skrovina, Matej; Bencurik, Vladimir; Martinek, Lubomir; Machackova, Maria; Bartos, Jiri; Andel, Petr; Stepanova, Erika; Bunakova, Michaela; Vomackova, Katerina (Wideochirurgia i inne techniki maloinwazyjne, 2020)
INTRODUCTION: Anastomotic leak is a very serious complication in colorectal surgery. Tissue perfusion of the anastomosis plays an integral role in its multifactorial etiology. Fluorescence angiography using indocyanine green allows visualization of perfusion in real time. AIM: To evaluate the effectiveness of intraoperative fluorescence angiography as a tool to decrease the incidence of anastomotic leak after laparoscopic or robotic low resection of the rectum for cancer. MATERIAL AND METHODS: Intraoperative fluorescence angiography was performed sequentially in 50 patients during low rectal resection for cancer with total mesorectal excision, primary anastomosis and protective ileostomy using laparoscopic or robotic technique. The results were compared to a historical control group of 50 patients with the same procedure without the use of fluorescence angiography. RESULTS: The patient sets were comparable in basic demographic and clinical parameters. Intraoperative visualization of perfusion by fluorescence angiography was achieved in all patients without unwanted side-effects. In 6 (12%) patients, the resection line was adjusted based on the fluorescence angiography. The incidence of anastomotic leak was insignificantly lower in the group with fluorescence angiography (18% vs. 10%), which led to significantly shorter hospital stay. Other postoperative complications were comparable between the two groups. CONCLUSIONS: Fluorescence angiography using indocyanine green is a safe and effective method with the potential of reducing anastomotic leak during minimally invasive low resection of the rectum for cancer.
Keywords: indocyanine green; rectal cancer; anastomotic leak; fluorescence angiography